1991
DOI: 10.1088/0960-1317/1/3/002
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-to-silicon anodic bonding with a borosilicate glass layer

Abstract: Anodic bonding of silicon wafers by sputter deposited glass films, silicon-to-silicon anodic bonding, is presented as a promising sealing method in microengineering. A reliable process for wafer-to-wafer bonding is described and data concerning yield and bonding strength are given. Cathodic bonding is reported in a discussion about the bonding mechanism. Different sputter deposited and annealed Pyrex 7740 layers are evaluated as sealing material. Some advantages of silicon-to-silicon anodic bonding as a mounti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…Several bonding methods, such as anodic bonding (Nese and Hanneborg 1993), direct bonding (Harendt et al 1991;Hunt et al 1991), and intermediate layer bonding (Legtenberg et al 1999;Hanneborg et al 1991), have been reported for the joining and sealing of Si-based microdevices. Among these methods, applying thin film intermediate layers on one or both component surfaces can help lower the bonding temperature, which may serve to minimize feature distortions when microscale structures are bonded.…”
Section: Introductionmentioning
confidence: 99%
“…Several bonding methods, such as anodic bonding (Nese and Hanneborg 1993), direct bonding (Harendt et al 1991;Hunt et al 1991), and intermediate layer bonding (Legtenberg et al 1999;Hanneborg et al 1991), have been reported for the joining and sealing of Si-based microdevices. Among these methods, applying thin film intermediate layers on one or both component surfaces can help lower the bonding temperature, which may serve to minimize feature distortions when microscale structures are bonded.…”
Section: Introductionmentioning
confidence: 99%
“…Several bonding methods, such as anodic bonding (Nese and Hanneborg 1993), direct bonding (Harendt et al 1991;Hunt et al 1991), and intermediate layer bonding (Hanneborg et al 1991), have been reported for Si-based microsystems. Recently, we have reported successful bonding of Al-based HARMS with Al-Ge eutectic intermediate layers (Mei et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The glass layer, which is a few micrometers thick, is applied mostly by sputtering [7], but can also be produced by spin-on of a glass solution [8] or vapor deposition [9,10] upon a silicon wafer. These preparation techniques require defined process parameters in order for glass layers of the correct chemical composition, with sufficient adhesion to the substrate, and as free from stresses as possible to be produced.…”
Section: Introductionmentioning
confidence: 99%